2014
DOI: 10.1152/ajpgi.00315.2013
|View full text |Cite
|
Sign up to set email alerts
|

Colonic inflammation and secondary bile acids in alcoholic cirrhosis

Abstract: Alcohol abuse with/without cirrhosis is associated with an impaired gut barrier and inflammation. Gut microbiota can transform primary bile acids (BA) to secondary BAs, which can adversely impact the gut barrier. The purpose of this study was to define the effect of active alcohol intake on fecal BA levels and ileal and colonic inflammation in cirrhosis. Five age-matched groups {two noncirrhotic (control and drinkers) and three cirrhotic [nondrinkers/nonalcoholics (NAlc), abstinent alcoholic for >3 mo (AbsAlc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 35 publications
9
165
1
3
Order By: Relevance
“…Indeed, with the observation that CDCA inhibits Clostridium diffi cile spore germination, there is increasing interest in developing bile acid analogs that are resistant to bacterial transformations such as 7-dehydroxylation ( 196 ). Notably, levels of gut 7 ␣ / ␤ -dehydroxylation activity vary many fold between human populations ( 26 ) and under different pathophysiological conditions ( 197,198 ).…”
Section: Gut Microbiome Metabolism Of Bile Acidsmentioning
confidence: 99%
“…Indeed, with the observation that CDCA inhibits Clostridium diffi cile spore germination, there is increasing interest in developing bile acid analogs that are resistant to bacterial transformations such as 7-dehydroxylation ( 196 ). Notably, levels of gut 7 ␣ / ␤ -dehydroxylation activity vary many fold between human populations ( 26 ) and under different pathophysiological conditions ( 197,198 ).…”
Section: Gut Microbiome Metabolism Of Bile Acidsmentioning
confidence: 99%
“…There is an imbalance of BA synthesis and excretion in cirrhosis, with reduced levels of secondary BAs due to decreased colonic conversion (32,33). There is evidence that the Firmicutes, particularly those within the Clostridiales cluster, are responsible for the conversion of primary to secondary BAs in the colon (33)(34)(35). It is also possible that reduced BA secretion allows migration of oral microbiota downward to the distal gut, thereby potentiating small intestinal bacterial overgrowth.…”
Section: Cirrhosis Pathophysiology Including Gut Microbial Dysbiosismentioning
confidence: 99%
“…Recently, it has been reported that alcohol induces bile acid synthesis through activation of hepatic cannabinoid receptor type 1 (Cb1r) and CREBH (32). Kakiyama et al (2014) have shown that cirrhotic patients who are currently drinking have significantly higher levels of fecal secondary bile acids compared to cirrhotic patients abstaining from alcohol (> 6 months), nonalcoholic cirrhotics, drinkers without cirrhosis and even healthy control who abstain from alcohol (33). Cirrhotic patients actively drinking also showed significant increases in mRNA of proinflammatory markers (TNF-α, IL-6, IL-1β, MCP-1) in colonic but not ileal tissue compared with all other groups (33).…”
Section: Introductionmentioning
confidence: 99%